ENSURING FOOD SECURITY: INDIAN KNOWLEDGE SYSTEM AND LOCAL INNOVATION - Singh, Avantika (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The studies of NITI Ayog (2016), which highlight a discrepancy between the nutritional situation in India and the expanding Indian economy, show how unstable the health matrix is in India. Complementing the same worry, FAO (2018) underlines in its report "The State of Food Security and Nutrition in the World" India's perilous health situation. According to the assessment, almost 15% of the Indian population is undernourished and suspiciously anaemic. Considering the substantial challenges to food security in India, it is essential to recognize the potential for mediation via small-scale interventions aimed at alleviating hunger and malnutrition by enhancing food accessibility. These customs frequently originate from our robust traditional framework rooted on the principle of trusteeship. The study contends that public policy on the provision of delivery services to the local populations should draw insights from these local innovations, which offer valuable resources for addressing governance challenges. This paper examines Anaj Bank, a locally devised plan to solve food security gaps. Offering a rapid response in contrast to centralized food systems, it describes the significant deliberate interventions of the bank that can help consumption smoothing during food-deficient lean seasons and act as a first line of defense against food security shocks.